Economic Dependence And Political Change In Algeria 1962-1992 - Nacer, Youcef (2004)
This study introduces the theory of economic dependence and applies the standard indicators, developed by economists in the past five decades, to the Algerian economic situation since its independence from France in 1962. It shows how the economic dependence in Algeria contributes to its political dependence, and to political changes that deviate from historical national norms. This is especially demonstrated in the case of the recent Algerian crisis, in which over 100,000 lives have been lost.. This analyhcal perspective argues that Algeria's current economic problems are primarily caused by Algeria's economic dependence on France and other Western capitalist countries. The internal political instability that has subsequently occurred is a direct result of the imbalance that exists in its foreign trade and international relations. A factual basis is presented to show how Algeria's political malaise is intimately associated with its external economic dependence. The Algerian dependence, characterised by foreign asset accumulation and foreign dominance in the major industries, has accelerated in recent years. This status of subordination in Algeria and the methods used to achieve and maintain it ilustrate a common pattern This pattern is found in other developing countries, and is seen to be the result of intentional policies and activities of the major countries. Economic dependence has, as its main feature, a basis of inequality and imbalance in foreign trade that is unfair to the smaller, economically weaker countries. The outcome of this long historical process, in which different means and tools were used; is demolition of the national will of the dependent country. The local population is weakened of most of its control and power by imposing conditions that punish those who advocate reformation and progress toward economic and political independence. The status of economic dependence has led to negative political change, one that is very inimical to the civilisational and historical legacy of the Algerian people. The developed countries exploit the weak economic situation of developing countries such as Algeria, exerting unfBir pressure on these countries to implement a warped and unrealistic version of Western democracy. Where subert methods opf political control fail, military means are used, to destroy the democratic process, and install military dictatorships. Unfortunately, this effort has significant negative implications, for the military governments installed escalate the economic problems and invite conditions that bring tense social and political stress. The military regime change approach leads to civil war, such as the one that took place in Algeria in 1992. This is our area of concern.